2014
DOI: 10.1021/cg4016355
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Thermal Stability of Amylose–Lipid Complexes: A Case Study on Amylose–Glycerol Monostearate

Abstract: Three different crystalline amylose−glycerol monostearate (GMS) complexes with increasing thermal stability can be distinguished: type I, type IIa, and type IIb. All complexes consist of GMS-loaded amylose helices that pack hexagonally into lamellar habits. The complex melting points are proportional to the thickness of the lamellae and depend on the amount of water in the system. For type I complexes, SAXS experiments reveal folded amylose chains and a lamellar thickness governed by the presence of two stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 54 publications
0
31
0
2
Order By: Relevance
“…Similar values of AMLC form I (average ∆ H [RS5‐I] 0.16 J/g) suggests that the amount of this amylose complex in all treatments was similar and differed only in the variety of species as revealed by a different range of temperature (Table ). The 4th endotherm corresponds to AMLC form II and was observed at higher temperatures (110 to 130 °C) compared to the AMLC form I (Goderis and others ). According with Tufvesson and others (), if type I complexes are annealed at high temperature (>90 °C), they are transformed into type II complexes.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar values of AMLC form I (average ∆ H [RS5‐I] 0.16 J/g) suggests that the amount of this amylose complex in all treatments was similar and differed only in the variety of species as revealed by a different range of temperature (Table ). The 4th endotherm corresponds to AMLC form II and was observed at higher temperatures (110 to 130 °C) compared to the AMLC form I (Goderis and others ). According with Tufvesson and others (), if type I complexes are annealed at high temperature (>90 °C), they are transformed into type II complexes.…”
Section: Resultsmentioning
confidence: 85%
“…Native lipids in cereal starch granules are mostly free fatty acids and lysophospholipids, although the content of lipids in cereal starch granules is positively correlated with the amylose content of starch (Morrison and others ). AMLC form I is formed after gelatinization of starch in the presence of endogenous or added lipids (Goderis and others ). This endotherm was reported in tamales by Figueroa and others ().…”
Section: Resultsmentioning
confidence: 99%
“…Pt was negatively correlated with linoleic acid ( r = −0.55) and linolenic acid ( r = −0.58) ( p < 0.01) but positively correlated with palmitoleic acid ( r = 0.45), arachidic acid ( r = 0.43) ( p < 0.05), stearic acid ( r = 0.51), oleic acid ( r = 0.51), icoscenoic acid ( r = 0.60), behenic acid ( r = 0.65), and libnoceric acid ( r = 0.54) ( p < 0.01). The dissociation temperature of ALCs increased with increasing chain length of the fatty acids, but dissociation enthalpy was practically independent of chain length (Goderis, Putseys, & Gommes, ; Raphaelides & Karkalas, ) showed that three different crystalline amylose−glycerol monostearate complexes with increasing thermal stability can be distinguished: type I, type II, and type IIb and that complex melting points are proportional to the thickness of the lamellae and depend on the amount of water in the system.…”
Section: Resultsmentioning
confidence: 99%
“…Lipids or emulsifiers are commonly used in the formulations of many foods to improve processing and the quality of the final food products. Starch, especially its linear amylose fraction, can interact with endogenous or added lipids to form single-helix complexes, which have been well characterized at different molecular levels (Goderis, Putseys, Gommes, Bosmans, & Delcour, 2014;Zabar, Lesmes, Katz, Shimoni, & Bianco-Peled, 2009;Zhang, Huang, Luo, & Fu, 2012). During starchy food processing, the formation of amylose-lipid complex can reduce the solubility of starch in water, alters the rheological properties of pastes, decrease swelling capacity, increase gelatinization temperature and decrease retrogradation and gel rigidity (Copeland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%